A STUDY OF THE EFFECT OF COMBINATION OF CEFTAZIDIME AND EDTA ON SOME TYPE OF BACTERIA ISOLATED FROM INFECTED WOUND. - ARWAM. ABDULLAH; RANA M.ABDULLAH (مجلة جامعة الانبار للعلوم الصرفة, 2012)
:A total of 100 swab samples were obtained from patients suffering from wound infection. The isolates were identified using different microscopical cultural characteristics and biochemical tests. Final identification of gram negative bacteria were performed by using API 20 E system. The most common bacteria isolates was Pseudomonas aeruginosa (37.64 %) followed by Staphylococcus aureus (23.52%). Escherichia coli and Klebsiella spp. (14.11%) each of them. Followed by Proteus mirabilis (8.23%), finally Enterococcus faecalis and Serratia marcesence (1.17%) each of them.Sensitivity of the isolates to antibiotic leveled high resistance to Amoxicillin, cefotaxime, ceftazidime, Gentamicin and Tobramycin. To less extent was the resistance to Ciprofloxacin, Amikacin, Cefepime, imipenem, norfloxacin, P-ofloxacin and Azitromycin. Combination of EDTA and ceftazidime gave interesting results against the local bacterial isolates.It was concluded from this study the possibility of using a combination of Ceftazidime with EDTA to treat infected wounds with high success rate